Pengaruh Environmental Awareness Terhadap Green Consumption Behavior: Peran Mediasi Pro-Environmental Behavior - Nesha Dwita Yohanes; Tri Kurniawati (Universitas Negeri Padang, 2026)
Climate change and the excessive exploitation of natural resources call for more responsible consumption patterns, particularly among university students. This study examines the influence of environmental awareness on green consumption behavior, both directly and through pro-environmental behavior as a mediating variable, among 381 students at Universitas Negeri Padang. The respondents were selected using proportional stratified random sampling, and the data were analyzed using a two-stage PLS-SEM approach. The results indicate that environmental awareness has a positive but relatively small direct effect on green consumption behavior (β = 0.140, p = 0.001), whereas its effect on pro-environmental behavior is substantially stronger (β = 0.526, p < 0.001). Furthermore, pro-environmental behavior is a strong predictor of green consumption behavior (β = 0.648, p < 0.001) and partially mediates the relationship between environmental awareness and green consumption behavior (indirect effect = 0.341; VAF =70.9%). These findings suggest that environmental awareness alone is insufficient to promote green consumption behavior unless it is translated into consistent proenvironmental practices. Therefore, universities should strengthen sustainability-oriented facilities and institutional policies to foster pro-environmental behavior and encourage sustainable consumption among students.